2018
DOI: 10.1149/2.0951802jes
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-Direct Synthesis of TiO2Nanoparticles by Plasma-Assisted Electrolysis with Enhanced Photocatalytic Performance

Abstract: A new plasma-assisted electrolysis method has been developed to synthesize amorphous TiO 2 nanoparticles and exploited for the enhanced photocatalytic performance. The method is simple, environmentally friendly, produces nanoparticles directly from bulk metal, and is suitable for mass production. The process was conducted in low-concentration nitric acid electrolyte under a voltage of 450 V, the minimum necessary to produce plasma on the anode surface. The average nanoparticle size was tuned between 16 and 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The next step was to obtain oxide structures of D elements. Aqueous solutions of metal salts and electrode materials in buffer solutions (to generate conductivity) were used as starting materials [11][12][13][14][15][16][17][18][19]. The results obtained showed that the method is quite promising, but to obtain pure structures it is necessary to wash or calcine the synthesis products.…”
Section: Introductionmentioning
confidence: 99%
“…The next step was to obtain oxide structures of D elements. Aqueous solutions of metal salts and electrode materials in buffer solutions (to generate conductivity) were used as starting materials [11][12][13][14][15][16][17][18][19]. The results obtained showed that the method is quite promising, but to obtain pure structures it is necessary to wash or calcine the synthesis products.…”
Section: Introductionmentioning
confidence: 99%